2006
DOI: 10.1021/ac0607616
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Quantitative Analysis of Metabolites Using Ion-Pair Liquid Chromatography−Electrospray Ionization Mass Spectrometry

Abstract: We have developed an analytical method, consisting of ion-pair liquid chromatography coupled to electrospray ionization mass spectrometry (IP-LC-ESI-MS), for the simultaneous quantitative analysis of several key classes of polar metabolites, like nucleotides, coenzyme A esters, sugar nucleotides, and sugar bisphosphates. The use of the ion-pair agent hexylamine and optimization of the pH of the mobile phases were critical parameters in obtaining good retention and peak shapes of many of the above-mentioned pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
155
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(161 citation statements)
references
References 22 publications
2
155
0
Order By: Relevance
“…The poly(ADPribosyl)ated PARP1 was treated with PARG, and the mixture filtered using centricons (30 kDa cutoff). The analysis of the filtrate was performed using a modified procedure by Coulier et al 26 , which employed ion-pair chromatography for the separation of nucleotides and negative electrospray ionization for the mass spectrometric detection. All analyses were performed using a Waters Acquity UPLC system (Waters Corp., Milford, MA, USA) coupled to a QTOF Premier mass spectrometer (Waters Micromass, Manchester, UK).…”
Section: Parg Inhibition Assaymentioning
confidence: 99%
“…The poly(ADPribosyl)ated PARP1 was treated with PARG, and the mixture filtered using centricons (30 kDa cutoff). The analysis of the filtrate was performed using a modified procedure by Coulier et al 26 , which employed ion-pair chromatography for the separation of nucleotides and negative electrospray ionization for the mass spectrometric detection. All analyses were performed using a Waters Acquity UPLC system (Waters Corp., Milford, MA, USA) coupled to a QTOF Premier mass spectrometer (Waters Micromass, Manchester, UK).…”
Section: Parg Inhibition Assaymentioning
confidence: 99%
“…A successful and robust application of hexylamine as an ion pairing reagent together with a careful control of mobile phase pH has been described for acidic metabolites retention and detection with LC-negative-ESI-MS. In this case, no interference was observed from hexylamine as it is a volatile reagent and ionizes only in the positive mode (Coulier, Bas et al 2006). With a similar ion pairing reagent, dimethylhexylamine, a switch from the negative to the positive ESI is possible, which increases the sensitivity and selectivity of the method (Pruvost, Théodoro et al 2008).…”
Section: Ion-pairing Reagentsmentioning
confidence: 91%
“…Recently, rapidly growing reports demonstrated that microbial metabolomics could provide more data and describe higher complex metabolite profiles (Oldiges et al, 2007;Wu et al, 2008;Tang et al, 2009). Typical detection methods in metabolome analysis include gas chromatography-mass spectrometry (GC-MS), liquid chromatography (LC)-MS, and nuclear magnetic resonance spectroscopy (NMR), which offer higher sensitivity and the ability to detect a larger number of low-molecular weight metabolites (van Dam et al, 2002;Coulier et al, 2006;Koek et al, 2006). Accordingly, further studies on metabolomics could contribute to a better understanding on the necessary role of L. bulgaricus in fermentation.…”
Section: Introductionmentioning
confidence: 99%